Pengaruh Modifikasi Permainan Zig-Zag Run terhadap Peningkatan Keterampilan Dribbling Pemain Futsal Triad Abadi Usia 12 Tahun - Kaka Kustiana; Ayi Suherman; Tedi Supriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of modified zig-zag run games on improving the dribbling skills of 12-year-old Triad Abadi futsal players. The research method used was a pre-experimental design with a One Group Pretest–Posttest Design. The population consisted of elementary school–aged futsal players participating in training at the Triad Abadi futsal club in Rancakalong, Sumedang. The sample included 20 players selected using purposive sampling, with criteria including approximately 12 years of age, active participation in training, and no injuries that could hinder training activities. The research instrument used a zig-zag dribbling skill test to measure ball control, agility, and change-of-direction ability while dribbling. The research procedure included a pretest, followed by a treatment in the form of modified zig-zag run training for 6 weeks with a frequency of three training sessions per week, and ended with a posttest. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, and Paired Sample t-test with SPSS software. The results showed a significant improvement in dribbling skills after the treatment, indicated by a significance value (Sig. 2-tailed) of 0.000 (< 0.05). The mean score decreased from 19.70 in the pretest to 17.76 in the posttest, indicating an improvement in players' dribbling performance. Therefore, the modified zig-zag run game is proven to be effective in improving the dribbling skills of 12-year-old futsal players. Keywords: Agility, Dribbling, Futsal, Game Modification, Zig-Zag Run